Tunezyjskie wspólnoty pasterskie jako wspólnoty komunikacyjne - Oueslati, Jamila (Scripta Neophilologica Posnaniensia, 2022)
This article examines Tunisian pastoralists in light of the theory of communicative communities. The pastoral reality occurs as a stream of events that appear and disappear in the multi-dimensional pastoral reality. Each such dimension, or parameter thereof is a system of homogenous characteristics, reflecting essential aspects of the diverse pastoral experience. Tunisian pastoralism can be understood as the family comprised of all Tunisian pastoral communities. The contents of this article were ordered with a framework of two components – terminological and postulative. The first is devoted to a definition of terms which reveal the linguistic and cultural richness of the pastoral community, simultaneously providing insight into the conceptual content of the theoretical undertaking proposed here. The postulative component, on the other hand, takes up the relations between the objects denoted by the terms defined with the help of a system of postulates which reflect the propositional content of this work. Although the article, of necessity, treats only selected aspects of Tunisian pastoral reality, it does, however, present the linguistic and cultural specifics of the Tunisian pastoral community.